SELF-EFFICACY AND ABILITY TO PERFORM ACTIVITIES OF DAILY LIVING (ADL) IN APPENDICECTOMY POST-OPERATIVE PATIENTS - Iswatun Qasanah; Futkhatin Nasikhah; Heny Siswanti; Muhamad Jauhar (Universitas Muhammadiyah Kudus, 2024)
The incidence of appendicitis in Indonesia ranks highest among other abdominal emergencies. The cause is usually an obstruction in the lumen of the appendix and causes acute inflammation with perforation and abscess formation. Treatment of appendicitis can be done by surgery. Postoperative recovery restores normal physical, psychological, social, habitual, and daily activities. The ability to perform Activities of Daily Living (ADL) depends on cognitive, motor, and perceptual abilities, which can affect postoperative patients in mobilizing is a psychological factor, one of which is self-efficacy; someone who can mobilize early requires strong or high self-efficacy. This study aims to analyze the relationship between self-efficacy and ADL in appendicectomy postoperative patients. This study used a correlational research design using a cross-sectional approach and purposive sampling technique. The variables in this study were self-efficacy and ADL ability of appendicectomy postoperative patients. This research was conducted at Sunan Kalijaga Demak Hospital in August 2024. The sample obtained was 57 people who met the criteria. This research instrument uses the General Self-Efficacy (GSE) questionnaire and the Care Dependency Scale (CDS) questionnaire—data analysis using the Spearman Rank Test statistical test. Based on the results of this study, we obtained a p-value of 0.351 (p0.05). It can be concluded that there is a relationship between self-efficacy and ADL in postoperative patients at Sunan Kalijaga Demak Hospital. The results of this study can provide input to the nursing profession that self-efficacy can improve Activity of Daily Living (ADL) in postoperative patients.